Combination of ginsenoside Rg3 with docetaxel enhances the susceptibility of prostate cancer cells via inhibition of NF-κB - Kim, Sun Mi; Lee, So Yong; Cho, Jin Suk; Son, Seung Mo; Choi, Sang Sook; Yun, Yeo Pyo; Yoo, Hwan Soo; Yoon, Do Young; Oh, Ki-Wan; Han, Sang Bae; Hong, Jin Tae (European journal of pharmacology, 2010)
Ginsenoside Rg3 has been a subject of interest for use as a cancer preventive or therapeutic agent. Nuclear factor-kappa (NF-κB) is constitutively activated in prostate cancer, and gives cancer cells resistance to chemotherapeutic agents. To investigate whether Rg3 can suppress the activation of NF-κB, and thus increase susceptibility of prostate (LNCaP and PC-3, DU145) cells against chemotherapeutics, prostate cancer cell growth as well as activation of NF-κB was examined. We found that a combination treatment of Rg3 (50 µM) with a conventional agent docetaxel (5 nM) was more effective in the inhibition of prostate cancer cell growth and induction of apoptosis as well as G 0/G 1 arrest accompanied with the significant inhibition of NF-κB activity than those by treatment of Rg3 or docetaxel alone. It was also found that NF-κB target gene expression of Bax, caspase-3, and caspase-9 was much more significantly enhanced, but the expression of Bcl-2, inhibitor of apoptosis protein (IAP-1) and X chromosome IAP (XIAP), and the expression of cell cycle regulatory proteins cyclin B, D1 and E, and cyclin dependent kinases 2 and 4 was also much more significantly inhibited by the combination treatment. The combination of Rg3 (50 µM) with cisplatin (10 µM) and doxorubicin (2 µM) was also more effective in the inhibition of prostate cancer cell growth and NF-κB activity than those by the treatment of Rg3 or chemotherapeutics alone. These results indicate that ginsenoside Rg3 inhibits NF-κB, and enhances the susceptibility of prostate cancer cells to docetaxel and other chemotherapeutics. Thus, ginsenoside Rg3 could be useful as an anti-cancer agent.